2022
DOI: 10.3390/toxins14020068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Resistance, and Whole Genome Sequencing Analysis of Shiga Toxin-Producing Escherichia coli (STEC) and Enteropathogenic Escherichia coli (EPEC) from Imported Foods in China during 2015–2021

Abstract: Shiga toxin-producing Escherichia coli (STEC) and enteropathogenic Escherichia coli (EPEC) are foodborne pathogens that cause hemolytic uremic syndrome and fatal infant diarrhea, respectively, but the characterization of these bacteria from imported food in China are unknown. A total of 1577 food samples from various countries during 2015–2021 were screened for STEC and EPEC, and the obtained isolates were tested for antimicrobial resistance and whole genome sequencing analysis was performed. The prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Moreover, the frequency of these diarrheagenic strains in poultry or carcasses was higher than that found in other studies. Hence, EPEC strains continue to be the most prevalent when compared to STEC strains (Dutta et al, 2011;Alonso et al, 2012;Samanta et al, 2015;Badi et al, 2018;Cerutti et al, 2020;Shen et al, 2022), which was corroborated by the same reports. Nonetheless, this differs from reports by Nagwa et al, (2022), where 30% of STEC and 10% of EPEC were found.…”
Section: Epec and Stec Characterizationmentioning
confidence: 70%
“…Moreover, the frequency of these diarrheagenic strains in poultry or carcasses was higher than that found in other studies. Hence, EPEC strains continue to be the most prevalent when compared to STEC strains (Dutta et al, 2011;Alonso et al, 2012;Samanta et al, 2015;Badi et al, 2018;Cerutti et al, 2020;Shen et al, 2022), which was corroborated by the same reports. Nonetheless, this differs from reports by Nagwa et al, (2022), where 30% of STEC and 10% of EPEC were found.…”
Section: Epec and Stec Characterizationmentioning
confidence: 70%
“…This result was in line with Awad et al [ 41 ] who reported ETEC/STEC (14.7%) and ETEC/EPEC (2.7%) in diarrheic calves in Egypt. Other researchers showed that diarrheic calves could be infected with a hybrid STEC-ETEC pathotype [ 50 , 51 ]. These pathogroups are characterized as hetero-pathotypes comprised of virulence genes representing two or more E. coli pathotypes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foodborne organisms such as Shiga toxin-producing E. coli (STEC) can cause watery, bloody diarrhea, hemorrhagic colitis, and potentially fatal hemolytic uremic syndrome (HUS). Shiga toxins are divided into two subfamilies, Stx1 and Stx2 , and are encoded by stx1 and stx2 are the primary virulence factors of STEC [ 1 ]. They are pathogenic by adhering to and causing effacement lesions in the intestinal microvilli of the host cell.…”
Section: Introductionmentioning
confidence: 99%